Relationship between government quality, economic growth and income inequality: Evidence from Vietnam - Nguyen Thanh Hung; Nguyen Thi Hoang Yen; Le Doan Minh Duc; Vo Hoang Ngoc Thuy; Nguyen Thanh Vu (Cogent Business & Management, 2020)
Government quality, economic growth and income inequality are topics that are of interest to many researchers, especially in Vietnam-a country with high economic growth and income inequality, and the quality of government is not fully transparent. Moreover, these three topics are only experimentally conducted separately and have not been explored simultaneously. This study analyzed the concurrent relationship between government quality, economic growth and income inequality within Vietnam in the period 2006-2017 with Stata tool with 3-stage regression model. The results show that higher government quality will boost economic growth and reduce inequality among provinces. On the other hand, economic growth can improve government quality but increase income inequality among provinces. This implies that the government and public administration executives will have a full perspective to assess and predict macro policies and make reference for further studies.
Keywords: 650; Government quality; public administration; economic growth; income inequality